Faktor-faktor penyebab terjadinya karsinoma nasofaring (KNF) - Amanah, Nur Suci (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Nasopharyngeal carcinoma is a common disease in southern China. The etiologies of the main factors proposed for the pathogenesis of KNF include genetic factors, environmental factors and Epstein Barr Virus (EBV) infection. Other causes besides preserved food consumption include salted fish which have been involved in the etiology of NPC. The downward trend in the incidence of NPC has occurred in Hong Kong for the past 20 years, which is caused by changes in dietary habits. Despite the close relationship of EBV infection with NPC, the etiological role of EBV in the pathogenesis of NPC remains an interaction. EBV infection in primary nasopharyngeal epithelial cells occurs. Epstein Barr virus does not convert primary nasopharyngeal epithelial cells into proliferative clones, which is in sharp contrast to the well-documented ability of EBV to alter and perpetuate primary B cells. Genetic changes that are supported in the nasopharyngeal epithelium may be needed to support stable EBV infection. Non-viral factors as a cause of nasopharyngeal carcinoma still cannot be resolved with certainty. Non-viral factors are one of the risk factors that can increase the number of events arising from nasopharyngeal malignancies such as smoke, salted fish, formaldehyde, genetic, as soon as possible firewood, wood dust, chronic infection, throat protector, alcohol and traditional medicine.